The origin and evolution of the Peace Vallis fan system that drains to the Curiosity landing area, Gale Crater, Mars. Issue 4 (4th April 2014) - Palucis, Marisa C.; Dietrich, William E.; Hayes, Alexander G.; Williams, Rebecca M. E.; Gupta, Sanjeev; Mangold, Nicholas; Newsom, Horton; Hardgrove, Craig; Calef, Fred; Sumner, Dawn Y.
Abstract The landing site for the Curiosity rover is located at the distal end of the Peace Vallis fan in Gale Crater. Peace Vallis fan covers 80 km2 and is fed by a 730 km2 catchment, which drains an upland plains area through a 15 km wide gap in the crater rim. Valley incision into accumulated debris delivered sediment through a relatively low density valley network to a main stem channel to the fan. An estimated total fan volume of 0.9 km3 matches the calculated volume of removal due to valley incision (0.8 km3) and indicates a mean thickness of 9 m. The fan profile is weakly concave up with a mean slope of 1.5% for the lower portion. Numerous inverted channels outcrop on the western surface of the fan, but on the eastern portion such channels are rare suggesting a change in process from distributary channel domination on the west to sheet flow on the eastern portion of the fan. Runoff (discharge/watershed area) to produce the fan is estimated to be more than 600 m, perhaps as much as 6000 m, indicating a hydrologic cycle that likely lasted at least thousands of years. Atmospheric precipitation (possibly snow) not seepage produced the runoff. Based on topographic data, Peace Vallis fan likely onlapped Bradbury Rise and spilled into a topographic low to the east of the rise. This argues that the light‐toned fractured terrain within this topographic low corresponds to the distal deposits of Peace Vallis fan, and in such a setting, lacustrine deposits are expected.